2019
DOI: 10.1017/ice.2019.205
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of central-line–associated bloodstream infection (CLABSI) diagnostic reliability and error

Abstract: Objective:To establish the reliability of the application of National Health and Safety Network (NHSN) central-line–associated bloodstream infection (CLABSI) criteria within established reporting systems internationally.Design:Diagnostic-test accuracy systematic review.Methods:We conducted a search of Medline, SCOPUS, the Cochrane Library, CINAHL (EbscoHost), and PubMed (NCBI). Cohort studies were eligible for inclusion if they compared publicly reported CLABSI rates and were conducted by independent and exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Whereas the incidence of BSI may appear high within this study, BSI incidence reported here includes central line-associated bloodstream infection (CLABSI) along with bloodstream infections associated with other primary infections and those with undefined sources that meet the ECDC case definitions. A recent review has also indicated that CLABSI is likely underreported nationally when compared to expert review using consistently applied case definitions [42]. The specialties with the highest recorded incidence per 100,000 bed-days were ICU, renal medicine, and cardiothoracic surgery (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the incidence of BSI may appear high within this study, BSI incidence reported here includes central line-associated bloodstream infection (CLABSI) along with bloodstream infections associated with other primary infections and those with undefined sources that meet the ECDC case definitions. A recent review has also indicated that CLABSI is likely underreported nationally when compared to expert review using consistently applied case definitions [42]. The specialties with the highest recorded incidence per 100,000 bed-days were ICU, renal medicine, and cardiothoracic surgery (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…While specific definitions for entities such as CLABSI and sepsis exist in pediatrics, they often have inadequate sensitivity for clinically important infections and may be difficult to generalize across electronic medical record (EMR) platforms (7,8). Presumed serious infection (PSI), which is used in both adult and pediatric sepsis surveillance systems, is defined as a blood culture being obtained (regardless of the result) followed by new antimicrobial agents started within 2 days of the blood culture (i.e., agents that were not being administered prior to the blood culture) that are administered for at least 4 consecutive days or until time of death or transfer to another hospital (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…infections (HAI) are a main focus of infection prevention and control initiatives and are considered to be an important quality indicator in neonatal care [2][3][4]. Surveillance of CLABSI is essential to evaluate the success of preventive interventions and to measure trends over time [5][6][7]. Standardised CLABSI monitoring enables intra-and interfacility incidence rate comparisons which contributes to practice improvement [7,8].…”
mentioning
confidence: 99%
“…Surveillance of CLABSI is essential to evaluate the success of preventive interventions and to measure trends over time [5][6][7]. Standardised CLABSI monitoring enables intra-and interfacility incidence rate comparisons which contributes to practice improvement [7,8]. National registration systems of CLABSI have shown to be beneficial in this matter [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation